2019
DOI: 10.1177/1555458919874420
|View full text |Cite
|
Sign up to set email alerts
|

Educational Leadership in a Mayan Village in Southern Belize: Challenges Faced by a Mayan Woman Principal

Abstract: A Mayan woman principal taking a position in a historically paternalistic village in Southern Belize faces inevitable challenges due to the cultural structure of the village. In this case, the challenges go beyond cultural norms. Mrs. Po, a Mopan woman leading a school in a Kekchi village, faces challenges related to her role as a teaching principal in a multigrade school, her lack of leadership preparation, the remoteness of the village, and the language barrier, among others. The reader is encouraged to pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Education being 'wasteful' and 'too expensive' for women was repeated in Yanira Oliveras-Ortiz's research on education in Maya communities. According to Oliveras-Ortiz, education is perceived as unnecessary for their subsistence-farming community (Oliveras-Ortiz et al 2020). In this study Mrs. Po, a principal at a Mayan school, repeats the cultural preference for men to attain education, as it's believed that girls should stay home to look after younger siblings or start their own families (Oliveras-Ortiz et al 2020, p. 47).…”
Section: Machismo As a Catalyst For Q'eqchi' Women's Health Experiencesmentioning
confidence: 64%
“…Education being 'wasteful' and 'too expensive' for women was repeated in Yanira Oliveras-Ortiz's research on education in Maya communities. According to Oliveras-Ortiz, education is perceived as unnecessary for their subsistence-farming community (Oliveras-Ortiz et al 2020). In this study Mrs. Po, a principal at a Mayan school, repeats the cultural preference for men to attain education, as it's believed that girls should stay home to look after younger siblings or start their own families (Oliveras-Ortiz et al 2020, p. 47).…”
Section: Machismo As a Catalyst For Q'eqchi' Women's Health Experiencesmentioning
confidence: 64%
“…And despite dramatic shortages of qualified K-12 leaders in various school districts in Canada and the United States, few women are provided with the support to move up the ranks; without a distinct program to mentor qualified women for positions of authority, this shortage will continue (Tucker & Fushell, 2014). Indigenous women represent an abundant talent pool and are clearly willing to do the hard work needed to guide students and staff in challenging places and times (Oliveras-Ortiz & Hickey, 2020). Despite this need, as research has revealed, a systemic lack of opportunities and encouragement for indigenous women can keep them from finding roles in educational leadership.…”
Section: Support Systems For Indigenous Womenmentioning
confidence: 99%
“…This type of collaboration is vital to indigenous ways of leading and part of the reason women like those in the Mi’kmaw community are successful as educational leaders (Fitzgerald, 2003). In many indigenous and rural communities, balancing relationships between schools (institutions) and the community helps ease the way for women leaders who challenge cultural norms and gender stereotypes and are often not accepted within their own groups (Oliveras-Ortiz & Hickey, 2020). In fact, Oliveras-Ortiz and Hickey (2020) reveal that when female educational leaders leverage their connections to surrounding communities, they create more inclusive spaces and can boost their own acceptance in their leadership roles (Oliveras-Ortiz & Hickey, 2020).…”
Section: Support Systems For Indigenous Womenmentioning
confidence: 99%
See 2 more Smart Citations